33. RESULTS OF POSITIVE NUTRITIONAL SUPPORT ON PATIENTS WITH ESOPHAGEAL CANCER AT NGHE AN ONCOLOGY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of active nutritional support on the nutritional status of esophageal cancer patients at Nghe An Oncology Hospital.Materials and methods: This interventional study employed a pre-post evaluation on the same group, conducted on 63 esophageal cancer patients treated at Nghe An Oncology Hospital from 03/2024 to 09/2024.Results: The average age of patients was 60,9 ± 7,4 years, with 100% were male. The majority were in the late stages (III-IV), accounting for 92,1%, with 84,1% experiencing dysphagia symptoms. The rate of patients that lost >10% of their weight in 6 months was 44%. Post-intervention, the nutritional status of the patients improved significantly in terms of diet, with the rate of meeting recommended energy needs, increasing from 25,4% to 54%; Achieving the recommended amount of protein increased from 23,8% to 50,8% (p0,05).Conclusion:  Effective nutritional support plays a crucial role in reducing malnutrition risk in patients with esophageal cancer. Oncological patients need to be informed about the consequences of weight loss and low-threshold access to nutritional counseling needs to be comprehensively implemented.
Keywords: Esophageal cancer; malnutrition; PG-SGA